Modification & optimization of mechanical properties of bio fibers blended composites - Venkatesha Prasanna, G; ., . (International Journal of Engineering and Technology, 2018)
ABSTRACT: The synthetic fibers used possess some major hindrance with respect to machine abrasion, recyclability, non-renewable, environmentally safe, energy usage, & health problems. In the present work 10%, unsaturated polyester toughened with 90 % Epoxy is used as matrix blend. The Bio fibres used are Palmyra-Luffa fibres & the bio-composites were fabricated by reinforcing bio fibres with matrix blend using hand lay-up technique. The main intension of the work is to monitor the quantity of bio fibres for the manufacturing of high strength to weight & low cost natural fibers reinforced hybrid bio-composites for the automobile and manufacturing, marine and other industrial applications. The changes in the values of various mechanical properties like; impact, flexural and compressive properties at different quantity of untreated and alkali treated palmyra-Luffa fibers reinforced blended bio-composites have investigated. The changes in the various mechanical properties with respect to quantity of fiber content without and with surface modification have investigaed. At 40% quantity of surface modified palmyra-Luffa fibers the values of mechanical properties have found to be maximum when compared with 10%, 20%, 30%, and 50% quantity of surface modified composites and other untreated bio-composites. Chemical resistance test reveals that resistance towards various chemical was also improved appreciably for all the chemicals excluding carbon tetrachloride & toluene.Â Â